2020
DOI: 10.1371/journal.pone.0232826
|View full text |Cite
|
Sign up to set email alerts
|

Common gray and white matter abnormalities in schizophrenia and bipolar disorder

Abstract: This study aimed to investigate abnormalities in the gray matter and white matter (GM and WM, respectively) that are shared between schizophrenia (SZ) and bipolar disorder (BD). We used 3T-magnetic resonance imaging to examine patients with SZ, BD, or healthy control (HC) subjects (aged 20-50 years, N = 65 in each group). We generated modulated GM maps through voxel-based morphometry (VBM) for T1-weighted images and skeletonized fractional anisotropy, mean diffusion, and radial diffusivity maps through tract-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 65 publications
(85 reference statements)
1
28
0
Order By: Relevance
“…DTI studies of bipolar disorder have reported diffuse WM microstructural alterations[ 124 , 162 , 163 ], which are evident when tract integrity and WM volume are measured. Recent meta-analyses have found FA reductions in all major classes of WM tracts (commissural, association and projection fibers) with frequent reports of alterations in temporoparietal WM, the inferior fronto-occipital fasciculus, inferior longitudinal fasciculus, and left cingulum[ 124 , 164 ].…”
Section: Evidence Of Wm Alterations In Schizophrenia and Bipolar Diso...mentioning
confidence: 99%
“…DTI studies of bipolar disorder have reported diffuse WM microstructural alterations[ 124 , 162 , 163 ], which are evident when tract integrity and WM volume are measured. Recent meta-analyses have found FA reductions in all major classes of WM tracts (commissural, association and projection fibers) with frequent reports of alterations in temporoparietal WM, the inferior fronto-occipital fasciculus, inferior longitudinal fasciculus, and left cingulum[ 124 , 164 ].…”
Section: Evidence Of Wm Alterations In Schizophrenia and Bipolar Diso...mentioning
confidence: 99%
“…29 Indeed, previous structural, functional, and chemical imaging studies have reported neurodegeneration in the central nervous system of patients with BD. 4,5,30 Furthermore, the illness duration of BD correlated with the reduced thickness of the RNFL and GCL. 31,32 This was consistent with our finding that the BD group had a shorter duration from the time of enrollment to the diagnosis of a retinal disease than the control group.…”
Section: Discussionmentioning
confidence: 93%
“…Another study reported reduced thickness of RNFL and GCIPL in idiopathic retinal telangiectasia, a neurodegenerative retinal disease characterized by alterations in the macular capillary network, neurosensory atrophy, and occasional subretinal neovascularization 29 . Indeed, previous structural, functional, and chemical imaging studies have reported neurodegeneration in the central nervous system of patients with BD 4,5,30 . Furthermore, the illness duration of BD correlated with the reduced thickness of the RNFL and GCL 31,32 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our study, BD-II patients had a weaker SC connection between left PCG and left SFG vs. HCs. Studies regarding BD-I and BD-II as a whole found that FA in superior longitudinal fasciculus (SLF) was decreased in BD patients relative to HCs (70,71). SLF, as a major long association fiber tract, ipsilaterally connects parietal, frontal, temporal, and occipital cortices (67).…”
Section: Specific Alteration In Sc Connection Between Bd-ii and Hcsmentioning
confidence: 99%